Characterization of Corn Root Factors to Improve Artificial Diet for Western Corn Rootworm (Coleoptera: Chrysomelidae) Larvae. Issue 2 (6th April 2019) - Huynh, Man P; Bernklau, Elisa J; Coudron, Thomas A; Shelby, Kent S; Bjostad, Louis B; Hibbard, Bruce E
Abstract: The western corn rootworm, Diabrotica virgifera virgifera LeConte (Coleoptera: Chrysomelidae), is an important economic pest of maize ( Zea mays L.) in North America and Europe. Previous efforts to formulate an artificial diet for western corn rootworm larvae highlighted an important role of corn root powder, which had a significant positive impact on several larval developmental traits. Unfortunately, this ingredient is not available for purchase. Toward the goal of developing an artificial diet for western corn rootworm larvae with all ingredients readily accessible, we conducted research to isolate essential growth factors for larval development from corn root powder to improve the performance of diet without corn root powder. For all experiments, multiple life history parameters (survival, weight, and molting) were recorded from 15-d diet bioassays. Corn roots may contain factors that assist in larval growth, but some of these factors were not fully extracted by methanol and remained in the extracted root. Methanolic extracts significantly increased molting to second instar, but did not significantly increase survival, dry weight, or molting to third instar, suggesting the primary corn root substituents affecting these factors cannot be extracted or other extraction methods may be required to extract the essential factors from corn roots. We showed that whole corn root powder was best when used in combination with all the other nutrient sources in the published western corn rootworm formulation. Corn root powder made from proprietary seed and Viking seed has similar value.